Magnetic resonance imaging in patients with cardiac pacemakers: era of "MR Conditional" designs - Shellock Frank G; Colletti Patrick M; Shinbane Jerold S (Journal of Cardiovascular Magnetic Resonance, 2011)
Abstract Advances in cardiac device technology have led to the first generation of magnetic resonance imaging (MRI) conditional devices, providing more diagnostic imaging options for patients with these devices, but also new controversies. Prior studies of pacemakers in patients undergoing MRI procedures have provided groundwork for design improvements. Factors related to magnetic field interactions and transfer of electromagnetic energy led to specific design changes. Ferromagnetic content was minimized. Reed switches were modified. Leads were redesigned to reduce induced currents/heating. Circuitry filters and shielding were implemented to impede or limit the transfer of certain unwanted electromagnetic effects. Prospective multicenter clinical trials to assess the safety and efficacy of the first generation of MR conditional cardiac pacemakers demonstrated no significant alterations in pacing parameters compared to controls. There were no reported complications through the one month visit including no arrhythmias, electrical reset, inhibition of generator output, or adverse sensations. The safe implementation of these new technologies requires an understanding of the well-defined patient and MR system conditions. Although scanning a patient with an MR conditional device following the strictly defined patient and MR system conditions appears straightforward, issues related to patients with pre-existing devices remain complex. Until MR conditional devices are the routine platform for all of these devices, there will still be challenging decisions regarding imaging patients with pre-existing devices where MRI is required to diagnose and manage a potentially life threatening or serious scenario. A range of other devices including ICDs, biventricular devices, and implantable physiologic monitors as well as guidance of medical procedures using MRI technology will require further biomedical device design changes and testing. The development and implementation of cardiac MR conditional devices will continue to require the expertise and collaboration of multiple disciplines and will need to prove safety, effectiveness, and cost effectiveness in patient care.